CONSERVATION STATUS AND PROPAGATION OF Camellia dalatensis AND Camellia capitata BY CUTTINGS - En Le Hong; Duong Do Van; Doan Nguyen Pham; Phuc Nguyen Van; Cam Ngo Van; Hoa Le Thi Thuy; Trung Nguyen Ba; Hung Ho Si; Phi Ngo Giang; Nguyen Nguyen Thanh; Truong Hoang Thanh; Cuong Truong Quang (BIOTROPIA, 2024)
Article Highlights- Camellia dalatensis and Camellia capitata are critically endangered species.- Habitat loss and deforestation threaten the survival of these Camellia species.- Vegetative propagation aids conservation of critically endangered Camellia species.- Rooting success depends on cutting types, growth regulators, and substrate mix.- Research aids conservation efforts for Vietnam’s rare and vulnerable flora. AbstractCamellia dalatensis (V. D. Luong, Ninh & Hakoda) and Camellia capitata (Orel, Curry & Luu) are classified as critically endangered (CR) by the IUCN. Conservation solutions for these two species have not yet been fully implemented, while wild populations are declining. This research on vegetative propagation examined the efficacy of indole-3-butyric acid (IBA in solution or in powdered activated charcoal), cutting types (terminal shoot or stem cuttings), and substrates for the growth of cuttings (sand-coir dust mixes) on rooting efficiency. The highest rooting of C. dalatensis was observed in terminal shoot cuttings at 1,000 ppm IBA, and 25% sand and 75% coir dust substrate. Maximum values obtained were survival 95.6%, rooting percentage 88.9%, number of roots per cutting 6.9, root length 6.2 cm, and rooting index 42.9. For C. capitata, superior rooting was obtained with semi-hardwood cuttings, at 1,500 ppm IBA, and equal parts of sand and coir dust as substrate. Camellia capitata was more difficult to root, with maximum values of 65.6% survival, 52.2% rooting, 2.8 roots per cutting, 2.9 cm root length, and rooting index of 8.1. The results of this study can be used to support further propagation and conservation of these two endangered species.